GB1a Ameliorates Ulcerative Colitis via Regulation of the NF-κB and Nrf2 Signaling Pathways in an Experimental Model - Yu, Yuanyuan; Zheng, Congmin; Lu, Xu; Deng, Changsheng; Xu, Qin; Guo, Wenfeng; Wu, Qingye; Wang, Qi; Liu, Changhui; Huang, Xinan; Song, Jianping (Frontiers in Medicine, 2021)
Ulcerative colitis (UC) is an inflammatory bowel disease. The intake of African Garcinia Kola nuts has been reported as a therapy for diarrhea and dysentery in the African population. However, the mechanism of action through which Garcinia Kola nuts act to ameliorates UC remains unknown. GB1a is the main active component of Garcinia Kola nuts. In this study, we explored the therapeutic effects and underlying mechanism of GB1a on dextran sodium sulfate (DSS)-induced UC. Human Colonic Epithelial Cells (HCoEpic) were challenged with TNF-α to test the effects of GB1a in protecting against oxidative stress and inflammation in vitro. Our data showed that GB1a significantly attenuated DSS-induced colonic inflammatory injury manifested as reversed loss of body weight and disease activity index (DAI) scores in UC mice. We also showed that GB1a improved the permeability of the intestinal epithelium by modulating the expression of tight junction proteins (ZO-1, Occludin). Mechanistically, GB1a may activate the Nrf2 antioxidant signaling pathway and suppress the nuclear translocation of NF-κB in reduced oxidative stress and expression of inflammatory genes induced by TNF-α in HCoEpic cells. Our study suggests that GB1a alleviates inflammation, oxidative stress and the permeability of the colonic epithelial mucosa in UC mice via the repression of NF-κB and activation of Nrf2 signaling pathway.